Total Synthesis of the Caged Diterpenoid Atropurpuran - Xu, Jing (Synlett, 2022)
In this account, we wish to share some stories behind our 13-step synthesis of the caged complex diterpenoid atropurpuran. Although our approach might appear to have proceeded smoothly, the unraveling of the core-construction puzzle and late-stage decorations was full of drama.1 Introduction2 Total Synthesis of Atropurpuran3 Conclusion
Keywords: atropurpuran; diterpenoids; total synthesis; caged natural products; ring-closing metathesis; Diels–Alder reaction